2020
DOI: 10.5937/sjm15-21922
|View full text |Cite
|
Sign up to set email alerts
|

Moderating effect of demographic and business characteristics on performance of women owned small enterprises: Empirical evidence from India

Abstract: This study aims to explore the moderating effect of demographic and business characteristics on the performance of women-owned small enterprises. The theoretical and existing literature supports the moderating effect of demographic and business characteristics on business performance. The study adopted the descriptive research method. The primary data was gathered from 340 women owners of small enterprises and surveyed through a structured questionnaire. The Liner multiple regression was used to test the hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 49 publications
3
8
0
Order By: Relevance
“…Similar results were reported byAntoncic (2009) and Sagire Lucas (2017). It is also observed that the farm size has positively in uenced the agripreneurs' satisfaction echoing the ndings of Addo (2018), Richard et al (2021) andVasan (2020). In this study, marginal-level farmers make up most of the study population.…”
supporting
confidence: 82%
“…Similar results were reported byAntoncic (2009) and Sagire Lucas (2017). It is also observed that the farm size has positively in uenced the agripreneurs' satisfaction echoing the ndings of Addo (2018), Richard et al (2021) andVasan (2020). In this study, marginal-level farmers make up most of the study population.…”
supporting
confidence: 82%
“…Next research (Safrianto, 2020) with the title study influence Skills entrepreneurship and experience effort to success entrepreneurship state that experience capable bring SMEs _ to avoid risk failure effort. Then (Vasan, 2020) under the title study Moderating Effect of Demographic and Business Characteristics on Performance of Women-Owned Small Enterprises: Empirical Evidence From India stated that experience Source Power Man take effect significant to the partnership. Implications findings in the study this that is that During this The experience possessed by SMEs is limited from results experience down hereditary.…”
Section: Influnce Experience Against the Partnership Programmentioning
confidence: 99%
“…women entrepreneurs(Onyusheva and Meyer, 2020;Vasan, 2020); and providing maternity support(Onyusheva and Meyer, 2020;Welsh et al, 2017b). For instance,Onyusheva and Meyer (2020) suggested the creation of parks or children's rooms in business centers, while Mehtap et al (2019) suggested supporting women that are mothers whose undertakes are informal.…”
mentioning
confidence: 99%
“…Brixiov a et al (2020),Caputo et al (2016),Cavada et al (2017),Ghani et al (2014),Hendratmi and Sukmaningrum (2018),Hernandez et al (2012),Lindvert et al (2017),Lock and Lawton Smith (2016),Maziriri et al (2019),Mbaruku and Mutalemwa (2015),Mehtap et al (2019),Olu- Owolabi et al (2020),Onyusheva and Meyer (2020),Ramadani et al (2013),Tlaiss and Kauser (2019),Vasan (2020),Welsh et al (2018Welsh et al ( , 2017aWelsh et al ( , 2017bWelsh et al ( , 2017a,Zainol et al (2017Zainol et al ( , 2018 Training Alene(2020), Batool and Ullah (2017), Hendratmi and Sukmaningrum (2018), Hernandez et al (2012), Langevang et al (2018), Ngoasong and Kimbu (2019), Onyusheva and Meyer (2020), Ramadani et al (2013), Reza et al (2020), Welsh et al (2017a, 2017b, 2017a, 2018), Zainol et al (2018) Providing access to resources Alene (2020), Batool and Ullah (2017), Brixiov a et al (2020), Ghouse et al (2017), Hendratmi and Sukmaningrum (2018), Hernandez et al (2012), Kimosop et al (2016), Mandongwe and Jaravaza (2020), Mbaruku and Mutalemwa (2015), Ngoasong and Kimbu (2019), Ramadani et al (2013), Siringi (2011), Vasan (2020), Welsh et al (2018, 2017a, 2017b) Decrease gender stereotypes Batool and Ullah (2017), Caputo et al (2016), Hernandez et al (2012), Roomi (2013), Siringi (2011), Welsh et al (2017a, 2017b) Change culture Hernandez et al (2012), Langevang et al (2018), Mehtap et al (2019), Siringi (2011), Welsh et al (2017a) Understand better the barriers women face Al-Dajani et al (2019), Ghouse et al (2017), Hernandez et al (2012), Jabeen and Faisal (2018) Lower the barriers women face Brixiov a et al (2020), Hernandez et al (2012), Tlaiss and Kauser (2019) Encourage familybusiness connections Olu-Owolabi et al (2020), Welsh et al (2017a), Xiong et al (2018) Promote mentoring Langevang et al (2018), Welsh et al…”
mentioning
confidence: 99%
See 1 more Smart Citation